Structural studies of icosahedral viruses - Zhang, H (2017)
Described as “organisms at the edge of life”, viruses are the most abundant type of biological entity that can infect all types of life forms and are found in almost every ecosystem on Earth. Although virus capsids can be found with a wide range of shapes, around half of the virus families have an icosahedral arrangement. This thesis mainly focuses on structural studies of proteins from two types of viruses: the VP5 protein of Bluetongue Virus (BTV) serotype 15, and the capsid protein (CP) of Maize Streak Virus (MSV) (the Nigerian strain). Bluetongue (BT) disease in ruminates is caused by BTV and is of important agricultural and economic impact. As one of the two proteins that comprise the outer capsid of the virus, VP5 has been shown to play an important role in membrane penetration. I describe structures of BTV VP5, at both high and low pH, both solved by X-ray crystallography to atomic resolution. These provide insights into the membrane penetration process for a non-enveloped virus at the molecular level. An atomic level mechanism of pH dependant conformation changes was revealed, including a re-arrangement of 3 bent helices into one long straight helix protruding out of the molecule, and a transformation from a β-sheet to an α-helix. The significant change due to the movement of the helix of the so-called unfurling domain could be caused by a conformation change of H386 pushing the conserved E316 residue in the so-called beam helix, α12, which contacts the anchoring domain. Our low pH structure fits well into the low pH cryo-EM image, clarifying the observed protruding density. Geminiviruses cause diseases in various plants, leading to great economic loss. MSV is the type member of genus Mastrevirus of the family Geminiviridae. The MSV capsid is composed of a single protein, termed, CP. Infectious virus particle capsids are generally constructed from two incomplete T=1 icosahedra, joined to form a so-called geminated viral particle of dimensions 220 x 380 Å with a fivefold symmetry axis coincident with the long axis, so that the CPs are arranged with quasi-icosahedral symmetry. The MSV VLP (single icosahedral particles) and the geminated MSV virion structures were solved to resolutions of 9.5 Å and 7.4 Å, respectively, by cryo-EM. A localized reconstruction method was used in the processing procedure in the geminated MSV virion structure by treating each half of the geminated particle (one incomplete icosahedral half) as a new single particle. These structures revealed structural information about the virus and help our understanding of the assembly of geminiviruses. The MSV geminated virus particles are characterized by a twinned icosahedral capsid with distorted peripentonal pentamers and equatorial pentamers observed by us, and a 12˚ offset between the two halves of the particle.